Empirical Description of Isotope Production in 0.01-2.5GeV p+natFe Reactions - Korakas, Kostantinos; Miliadou, Athanasia; Katsigianni, Theodora-Ilektra; Tasioudis, Diamantis; Nicolis, Nikolaos George (HNPS Advances in Nuclear Physics, 2022)
Experimental excitation functions of isotopes produced in reactions are compared with the results of empirical cross section formulas. We consider excitation functions of 16 isotopes (36Cl, 38Ar, 42,43K, 44Ti, 46,47,48Sc, 48,51Cr, 52Fe, 52,54Mn and 55,56,57Co) produced in reactions at bombarding energies from threshold up to 2.6 GeV. They are compared with the predictions of the empirical formulas of Rudstam, Silberberg-Tsao and SPACS. In the middle-energy range, the formulas provide (in the stated order) a progressively improved description of the experimental excitation functions of the dominant isotopes. At the highest energies, the limiting values of the dominant excitation functions are well described by the EPAX formula (Version 2.1). The predictive power of these formulas could be questioned at low energies close to the threshold, reaction products with a mass much smaller than the target and possibly low cross section channels.